Non-invasive respiratory support for infants with bronchiolitis: a national survey of practice. Issue 1 (December 2017) - Turnham, H.; Agbeko, R.; Furness, J.; Pappachan, J.; Sutcliffe, A.; Ramnarayan, P.
Abstract Background Bronchiolitis is a common respiratory illness of early childhood. For most children it is a mild self-limiting disease but a small number of children develop respiratory failure. Nasal continuous positive airway pressure (nCPAP) has traditionally been used to provide non-invasive respiratory support in these children, but there is little clinical trial evidence to support its use. More recently, high-flow nasal cannula therapy (HFNC) has emerged as a novel respiratory support modality. Our study aims to describe current national practice and clinician preferences relating to use of non-invasive respiratory support (nCPAP and HFNC) in the management of infants (<12 months old) with acute bronchiolitis. Methods We performed a cross-sectional web-based survey of hospitals with inpatient paediatric facilities in England and Wales. Responses were elicited from one senior doctor and one senior nurse at each hospital. We analysed the proportion of hospitals using HFNC and nCPAP; clinical thresholds for their initiation; and clinician preferences regarding first-line support modality and future research. Results The survey was distributed to 117 of 171 eligible hospitals; 97 hospitals provided responses (response rate: 83%). The majority of hospitals were able to provide nCPAP (89/97, 91.7%) or HFNC (71/97, 73.2%); both were available at 65 hospitals (67%). nCPAP was more likely to be delivered in a ward setting in a general hospital, and in a high dependency setting in a tertiary centre. There were differences in the oxygenation and acidosis thresholds, and clinical triggers such as recurrent apnoeas or work of breathing that influenced clinical decisions, regarding when to start nCPAP or HFNC. More individual respondents with access to both modalities (74/106, 69.8%) would choose HFNC over nCPAP as their first-line treatment option in a deteriorating child with bronchiolitis. Conclusions Despite lack of randomised trial evidence, nCPAP and HFNC are commonly used in British hospitals to support infants with acute bronchiolitis. HFNC appears to be currently the preferred first-line modality for non-invasive respiratory support due to perceived ease of use.